Fertility rates, course of pregnancy and perinatal outcomes after laparoscopic ureterolysis for deep endometriosis: A long-term follow-up study*. (17th August 2016) - Uccella, Stefano; Cromi, Antonella; Agosti, Massimo; Casarin, Jvan; Pinelli, Ciro; Marconi, Nicola; Bertoli, Francesca; Podesta'-Alluvion, Carolina; Ghezzi, Fabio
Abstract : We evaluated fertility rates, pregnancy course and maternal/neonatal outcomes following laparoscopic ureterolysis for deep endometriosis. Data about women who underwent laparoscopic excision of ureteral endometriosis were analysed. After exclusion of women who underwent hysterectomy/bilateral adnexectomy at initial surgery, and those lost-to-follow-up or with follow-up <1 year, a total of 61 patients were included. Of them, 36 (59%) wished to conceive after surgery. Twenty women became pregnant: nine (45%) of them after assisted reproductive technologies. Twenty-six pregnancies were observed with four (15.6%) miscarriages. Median gestational week at delivery was 38 weeks + 2 days (range, 33 + 1–41 + 6), with three (13.6%) and two (9%) deliveries before 37 and 34 weeks, respectively. Nine caesarean sections were performed (40.9%). Fertility rates after laparoscopic ureterolysis are comparable to those of other women operated for other forms of deep endometriosis. Apart from a higher risk of caesarean and preterm birth, the course of pregnancy and peripartum outcomes appear encouraging.